2005
DOI: 10.1159/000081979
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Protein Is a Useful Inflammatory Marker during Late-Onset Sepsis in Preterm Infants

Abstract: Background: Few studies demonstrated that serum amyloid A (SAA), a non-specific acute-phase reactant, could be used as a reliable early marker for the diagnosis of late-onset sepsis (LOS). Objectives: To evaluate the diagnostic value and the dynamics of SAA levels during the course of LOS and to compare it to those of other inflammatory markers. Methods: Levels of SAA, C-reactive protein (CRP) and IL-6 together with clinical variables, biochemical parameters and cultures retrieved from all preterm infants susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 23 publications
4
78
0
Order By: Relevance
“…SAA is known as an accurate inflammatory marker for the diagnosis and follow-up of late-onset sepsis in preterm infants [9][10][11] and has a greater sensitivity and specificity in reflecting inflammatory states. [16][17][18] We found that SAA has a high sensitivity and NPV at the time of sepsis evaluation, therefore can be used as a sensitive marker for the detection of EOS, not missing genuine cases of EOS when levels of SAA remain low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAA is known as an accurate inflammatory marker for the diagnosis and follow-up of late-onset sepsis in preterm infants [9][10][11] and has a greater sensitivity and specificity in reflecting inflammatory states. [16][17][18] We found that SAA has a high sensitivity and NPV at the time of sepsis evaluation, therefore can be used as a sensitive marker for the detection of EOS, not missing genuine cases of EOS when levels of SAA remain low.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that SAA has a better diagnostic accuracy than CRP and can be used in routine clinical work to diagnose, follow-up, and predict the outcome of late-onset sepsis in preterm infants. [10][11][12] Therefore, we aimed to evaluate the diagnostic accuracy of SAA in neonatal EOS at 0 and 24 h after birth. A comparison was drawn between the dynamics of SAA and CRP, an acute phase protein commonly used in EOS, and their association with the clinical course during the 48 h of EOS in term infants.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also stated that SAA levels had prognostic value in the first 24 h after the onset of neonatal sepsis. 31 They established that SAA had higher levels, and rose earlier and sharper than CRP. 10 In our study, we found that SAA had higher levels during the initial and 48-h evaluation of infants with sepsis.…”
Section: Saa Crp and Pctmentioning
confidence: 99%
“…These findings may suggest that culture positivity does not increase CRP, PCT or SAA levels in infants with neonatal sepsis. Arnon et al 11 found that SAA had significantly largest AUC compared with CRP at 0 h of sepsis evaluation. Enguix et al 22 reported that SAA, CRP and PCT had the same diagnostic efficiency and the same area under the ROC curve in neonates with bacterial sepsis.…”
Section: Saa Crp and Pctmentioning
confidence: 99%
See 1 more Smart Citation